Sedentary behaviour in college students and its influence on heart rate and mental health - Javier Magallón; Pilar Catalán (Asociación Española de Ciencias del Deporte, 2024)
Objective: To determine the relationship between sedentary lifestyle in university students and its relationship with physiological and psychological variables. Methods: This is a descriptive cross-sectional study, carried out in a sample of 376 university students belonging to the Teruel campus. The following variables were collected by means of questionnaires: anxiety, stress and sitting hours, and resting heart rate (HR) was measured. A correlation matrix using Pearson's coefficient in a linear regression model was used to test the association between variables. Results: Increased time in a sedentary position was related to increased levels of stress (p<0.001) and resting heart rate (p=0.014) independently of age. In addition, anxiety and stress also find a significant association(p<0.001). Higher self-perceived anxiety is related to higher stress levels. Only in those under 23 years of age is there a positive correlation between self-perceived anxiety and heart rate. That is, the higher the anxiety the higher the heart rate. Conclusions: The study showed that spending more time in a sedentary position generates negative consequences on students' health, such as increases in stress levels or resting heart rate, which could become an indirect risk of cardiovascular disease.